2022
DOI: 10.1101/2022.03.01.482492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic profiling and transfer dynamics of antibiotic resistance determinants in a full-scale granular sludge wastewater treatment plant

Abstract: In the One Health context, wastewater treatment plants (WWTPs) are central to safeguard water resources. Nonetheless, many questions remain about their effectiveness to prevent the dissemination of antimicrobial resistance (AMR). Most surveillance studies monitor the levels and removal of selected antibiotic resistance genes (ARGs) and mobile genetic elements (MGEs) in intracellular DNA (iDNA) extracted from WWTP influents and effluents. The role of extracellular free DNA (exDNA) in wastewater is mostly overlo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 75 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…Recently, we highlighted that the extracellular free DNA (exDNA) in wastewater is a rich pool of MGEs (65%; 5-9 µg exDNA L −1 ) [3] that can co-localize ARGs [4]. Quantifying DNA uptake from the environment by natural transformation is of key interest [5] since it can pose a risk for the development of ARB in wastewater environments and their discharge into nature and aquatic reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we highlighted that the extracellular free DNA (exDNA) in wastewater is a rich pool of MGEs (65%; 5-9 µg exDNA L −1 ) [3] that can co-localize ARGs [4]. Quantifying DNA uptake from the environment by natural transformation is of key interest [5] since it can pose a risk for the development of ARB in wastewater environments and their discharge into nature and aquatic reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Gram-positive ones have a thick peptidoglycan layer that absorbs antibiotics and detergents easier, leading to faster cell death and slower development of resistance [63]. We recently showed that most microorganisms co-localizing MGEs and ARGs in a full-scale WWTP were Gram-negative [4]. A diverse microbial community like activated sludge is composed of many potential hosts that encompass a diversity of mechanisms to maintain and transfer plasmids, including donor-mediated conjugation once the plasmid is transformed [64].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These compartments must be comprehensively taken into account when evaluating AR, following the One-Health approach (Miłobedzka et al, 2022). Wastewater treatment plants (WWTPs) should act as barriers to limit the spread of both, antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs), to the environment (Bürgmann et al, 2018; Calderón-Franco et al, 2022; Pallares-Vega et al, 2019). WWTP effluents, and wastewater catchment areas, are currently considered as one of the major release points of ARB and ARGs to the environment (Rizzo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a higher concentration (around 20%) of exDNA than iDNA has been detected in sediments in natural environments with nutrient scarcity (Mao et al, 2014). An increase (up to 2 log 10 gene copies mL -1 ) of some ARGs ( ermB and sul1 ) in the exDNA pool has been detected across a WWTP process, eventually discharged in the effluent (Calderón-Franco et al, 2022). The exDNA pool can therefore not be underestimated in AR surveillance in wastewater systems.…”
Section: Introductionmentioning
confidence: 99%